Training and Teaching Methods of Volunteer Teachers - Heflin, Houston (Christian education journal, 2014)
This article presents partial results from a self-report questionnaire of volunteer adult Bible class (Sunday school) teachers from Protestant churches across the United States. The survey questions sought to reveal the current teaching practices and methods of volunteer teachers as well as to identify the training needs of these teachers. Respondents (n = 121) were from 11 denominations in 15 states and were predominantly male. This article describes the results found about the number of years respondents have been teaching, frequency of teaching each year, hours they spend preparing to teach each week, size of classes they teach, type of curriculum they use, frequency of particular teaching methods, and types of training they have previously had and would welcome in the future. There was a mild relationship (r = .302, p < 0.001) between the total number of teaching methods used and the total number of training experiences teachers had experienced. Implications for equipping volunteer teachers are discussed.